The dynamic internet : how technology, users, and businesses are changing the network - Yoo, Christopher S. (AEI Press, 2010)
The Dynamic Internet: How Technology, Users, and Businesses are Changing the Network offers a comprehensive history of the Internet and efforts to regulate its use. University of Pennsylvania law professor Christopher S. Yoo contends that rather than engaging in prescriptive regulatory oversight, the government should promote competition in other ways, such as reducing costs for consumers, lowering entry barriers for new producers, and increasing transparency. These reforms would benefit consumers while permitting the industry to develop new solutions for emerging problems. It is fruitless for.